Experimental demonstration of suppression of low-frequency fluctuations and stabilization of an external-cavity laser diode - Rogister, F; Sukow, D W; Gavrielides, A; Mégret, P; Deparis, O; Blondel, M (Optics letters, 2000)
We demonstrate experimentally all-optical stabilization of a single-mode laser diode subject to external optical feedback operating in the low-frequency fluctuations (LFF) regime, by the technique of applying a second delayed optical feedback. We interpret our results as suppression of LFF through destruction of the antimodes responsible for the LFF crises and stabilization of the laser through creation of new maximum gain modes, in agreement with recent theoretical predictions.